Exploring Podophyllotoxin and Its Derivatives: Synthesis and Anticancer Developments - Chaudhary , Abha; Sharma , Deepak (Recent Developments in Science and Technology for Sustainable Future, 2024)
Many scientific studies have shown that plants are excellent source of useful bioactive substances. Sufficient proof of the healing properties of plants utilized in conventional medicine systems around the world can be found in scientific research. Lignans are the significant class of plant bioactive compounds from the pharmaceutical perspective and these are reported as folk medications in traditional medicines of China and Japan. Podophyllotoxin is one of the most well-known aryltetralin lignan due to its effectiveness in combating cancer. It is found in the Podophyllum plant species like P. hexandrum and P. peltatum rhizomes. Although podophyllotoxin is a strong antimitotic drug itself, it is too toxic for the human cancer therapy. Etoposide, teniposide, and etopophos the therapeutically significant anticancer drugs, are the semisynthetic derivatives of podophyllotoxin. These drugs have been used to cure many types of cancers, including lung, breast and testicular cancer. However, toxicity to the body, resistance to drugs and low absorption greatly restricted the use of these compounds in clinical therapy. However, in recent decades, substantial chemical modification and pharmacological research have been focused on the derivatives of podophyllotoxin to overcome these challenges and there is continuous search for more potent podophyllotoxin derivatives to treat a variety of malignancies. Thus our book chapter is focused on the importance of podophyllotoxin and its mode of action for cancer. Podophyllotoxin is found in Podophyllum plant species in rich amount but to maintain the ecological balance the commercially available podophyllotoxin is used for the chemical synthesis of its derivatives. We further discussed about about five well known derivatives of podophyllotoxin i.e. etoposide, teniposide, TOP 53, GL331 and NK611. The structures of podophyllotoxin and these derivatives are described along with their mechanisms of action. Very recent examples from 2021 onwards on the synthesis of C-4 and C-5 podophyllotoxin derivatives containing ester, piperazinyl-cinnamic amide moieties from podophyllotoxin are covered along with their anticancer potential.